2011
DOI: 10.1063/1.3541813
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of multiple bubble entrainment and interactions with two dimensional vortical flows

Abstract: Simulations of bubble entrainment and interactions with two dimensional vortical flows are preformed using a discrete element model. In this Eulerian-Lagrangian approach, solution to the carrier phase is obtained using direct numerical simulation whereas motion of subgrid bubbles is modeled using Lagrangian tracking. The volumetric displacement of the fluid by the finite size of the bubbles is modeled along with interphase momentum-exchange for a realistic coupling of the bubbles to the carrier phase. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
0
29
1
Order By: Relevance
“…The two systems of equations for the particles (equations (2.1)-(2.3)) and fluid (equations (2.20)-(2.21)) are coupled and solved in a structured Cartesian grid framework using a finite volume discretization and a pressure based second-order fractional time-stepping scheme based on the work of Finn et al (2011 and Cihonski et al (2013). Extensive validation of the method for dilute Natural sand dynamics in the wave bottom boundary layer bubble-and particle-laden flows has been reported in these works.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…The two systems of equations for the particles (equations (2.1)-(2.3)) and fluid (equations (2.20)-(2.21)) are coupled and solved in a structured Cartesian grid framework using a finite volume discretization and a pressure based second-order fractional time-stepping scheme based on the work of Finn et al (2011 and Cihonski et al (2013). Extensive validation of the method for dilute Natural sand dynamics in the wave bottom boundary layer bubble-and particle-laden flows has been reported in these works.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…(a) The previous work (Finn et al 2011) was a two-dimensional study and the present work is a full three-dimensional study. Although this in itself is a significant difference in the actual problem setting, this work also focuses on several new aspects of the bubble-vortex ring interactions and helps explore fundamental physics of this interaction by using two-phase flow modelling.…”
Section: Vortex-bubble Interactionmentioning
confidence: 99%
“…1.3. Problem description A travelling vortex ring, shown in figure 3(a), is generated through an inlet velocity pulse (Sridhar & Katz 1999;Finn et al 2011). This pulse forms a shear layer, which rolls up into a vortex ring that is convected downstream.…”
Section: Vortex-bubble Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other researchers focused on the bubble-vortex interactions rather than BBI. Finn et al 19 developed a discrete element model to simulate the bubble entrainment and interactions with two-dimensional vortical flows. It was found that the existence of the bubble resulted in the distortion of the vortex.…”
Section: Introductionmentioning
confidence: 99%